1998
DOI: 10.1111/j.1600-079x.1998.tb00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Pineal opioid receptors and analgesic action of melatonin

Abstract: Physicians have noted since antiquity that their patients complained of less pain and required fewer analgesics at night times. In most species, including the humans, the circulating levels of melatonin, a substance with analgesic and hypnotic properties, exhibit a pronounced circadian rhythm with serum levels being high at night and very low during day times. Moreover, melatonin exhibits maximal analgesic effects at night, pinealectomy abolishes the analgesic effects of melatonin, and mu opioid receptor antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 78 publications
1
54
1
1
Order By: Relevance
“…Melatonin has been associated with pain relief in patients with tissue injuries [11] and possesses antiinflammatory effects [12]. Although several findings have fueled speculation that melatonin affects pain sensitivity via an opiatergic mechanism [13], it is conceivable that melatonin may modulate variations in pain perception by affecting the activity of b-endorphin [14].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has been associated with pain relief in patients with tissue injuries [11] and possesses antiinflammatory effects [12]. Although several findings have fueled speculation that melatonin affects pain sensitivity via an opiatergic mechanism [13], it is conceivable that melatonin may modulate variations in pain perception by affecting the activity of b-endorphin [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that melatonin has analgesic effects through the opioid and benzodiazepine systems [Golombek et al, 1991;Ebadi et al, 1998;Jeong et al, 2000;Yu et al, 2000]. In most species, melatonin displays a circadian pattern with maximal level at night [Tamarkin et al, 1985].…”
Section: Discussionmentioning
confidence: 99%
“…Receptors or high affinity MEL binding sites were found in many tissues, indicating that MEL regulates physiological functions through a direct effect on these tissues. MEL synchronizes biological rhythms and exerts antioxidant (Tan et al 1993ab) and oncostatic (Hill and Blask 1988) properties; sedative, immunomodulative, analgetic, myorelaxing, cardioprotective and neuroprotective effects have been reported (Maestroni 1993;Reiter et al 1998;Lagneux et al 2000;Ebadi et al 1998;Vijayalaxmi et al 2002).…”
Section: Melatonin Prolonged Administration Metabolic Variables Shmentioning
confidence: 99%